Chronic kisspeptin delays puberty and reduces feed intake and body weight in female rats - Sriravali Sathagopam; Meenal Prabhakar Ullewar; Rakhi Harne; Sathya Velmurugan (The Korean Society of Animal Reproduction and Biotechnology, 2021)
Kisspeptin is a key player in the central control of reproductive axis. Central administration of kisspeptin has been shown to advance puberty in rats. Stimulation of hypothalamic GnRH pulse generating mechanism by kisspeptin has been proposed to be the mechanism behind the onset of puberty. We hypothesized that chronic high doses of kisspeptin administration suppresses the reproductive axis and hence delays the pubertal onset. Hence, we investigated the effect of peripheral administration of chronic high doses of kisspeptin on pubertal onset, feed intake and body weight in female rats. Rats were treated with saline or kisspeptin (100 nmoles per day; intraperitoneal) for 26 days (day 25 to day 50 postnatal) and the day of vaginal opening was marked as day of puberty. Kisspeptin treated rats had delayed pubertal onset and reduced feed intake and body weight. Gonadal GPR54 mRNA was reduced suggesting that chronic high doses of kisspeptin may suppress the reproductive functions possibly by downregulation of GPR54 receptor. However, delay in puberty due to reduction in feed intake and body weight could not be ruled out in this study. Further, our study emphasizes the importance of dosage and duration of kisspeptin administration in the manipulation of reproductive axis. Our study, for the first time, suggests that kisspeptin and its analogues, if proven beneficial, could be used to treat precocious puberty in children. It appears that, though a promising tool for enhancing fertility, kisspeptin acts as a double-edged sword and has to be cautiously used to manipulate reproduction.